Race, identity and work - Mickey, Ethel L.; Wingfield, Adia Harvey, 1977- (Research in the sociology of work, 2018)
This volume examines the connections between race and work, focusing on three key themes. First, contributors consider how racial minorities deal with questions of identity in the workplace. This is especially important as ideas about professionalism often hinge on implicitly racialized criteria, to an extent that racial identity may pose a challenge to meeting occupational requirements. Secondly, contributors address ways racial exclusion occurs in jobs in the new economy: while organizations can no longer legally segregate or discriminate on the basis of race, exclusion processes still occur in the contemporary workplace. Finally, this volume considers the strategies that minority workers use to combat and change patterns of workplace inequality. In the new economy, where workers arguably have limited power relative to organizations, the techniques of the past may not be as effective.Providing valuable insight on a growing segment of the labor force, this book considers the US's rapidly changing racial demographics and how this phenomenon fundamentally alters many aspects of work, providing an in-depth understanding of how race affects work for people of color across occupations, workplaces, and industries.